2019
DOI: 10.3389/fpls.2019.01425
|View full text |Cite
|
Sign up to set email alerts
|

Inheritance and Quantitative Trait Locus Mapping of Fusarium Wilt Resistance in Cucumber

Abstract: Fusarium wilt (FW) is a very serious soil-borne disease worldwide, which usually results in huge yield losses in cucumber production. However, the inheritance and molecular mechanism of the response to FW are still unknown in cucumber (Cucumis sativus L.). In this study, two inbred cucumber lines Superina (P1) and Rijiecheng (P2) were used as the sensitive and resistant lines, respectively. A mixed major gene plus polygene inheritance model was used to analyze the resistance to FW in different generations of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
2

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…for resistance is exclusively performed on foliar symptoms with a few on SVD (e.g., Ahmad et al, 2020;Alvarez et al, 2005;Bani et al, 2012;Branham et al, 2019;Chitwood-Brown et al, 2021;Dong et al, 2019;Leitão et al, 2020;Mahmoud & Abd El-Fatah, 2020;Miyatake et al, 2016;Pereira et al, 2020;Siamak & Zheng, 2018). This has been the case for cotton with wilt caused by most FOV other than FOV4 (Hillock, 1992;Sanogo & Zhang, 2016;Wang & Roberts, 2006;Wang et al, 1999;Zhang et al, 2015).…”
Section: Crop Sciencementioning
confidence: 99%
See 1 more Smart Citation
“…for resistance is exclusively performed on foliar symptoms with a few on SVD (e.g., Ahmad et al, 2020;Alvarez et al, 2005;Bani et al, 2012;Branham et al, 2019;Chitwood-Brown et al, 2021;Dong et al, 2019;Leitão et al, 2020;Mahmoud & Abd El-Fatah, 2020;Miyatake et al, 2016;Pereira et al, 2020;Siamak & Zheng, 2018). This has been the case for cotton with wilt caused by most FOV other than FOV4 (Hillock, 1992;Sanogo & Zhang, 2016;Wang & Roberts, 2006;Wang et al, 1999;Zhang et al, 2015).…”
Section: Crop Sciencementioning
confidence: 99%
“…We also suggested that MR and RVS should be combined to calculate disease severity rating (DSR) for a final accurate evaluation of cotton germplasm for FOV4 resistance (Zhang, Abdelraheem, Zhu, Wheeler, Dever, Elkins‐Arce et al., 2020). However, for almost all other crops with Fusarium wilt caused by different formae speciales of F. oxysporum , screening plants for resistance is exclusively performed on foliar symptoms with a few on SVD (e.g., Ahmad et al., 2020; Alvarez et al., 2005; Bani et al., 2012; Branham et al., 2019; Chitwood‐Brown et al., 2021; Dong et al., 2019; Leitão et al., 2020; Mahmoud & Abd El‐Fatah, 2020; Miyatake et al., 2016; Pereira et al., 2020; Siamak & Zheng, 2018). This has been the case for cotton with wilt caused by most FOV other than FOV4 (Hillock, 1992; Sanogo & Zhang, 2016; Wang & Roberts, 2006; Wang et al., 1999; Zhang et al., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…After 3 weeks, disease grades were recorded. The disease grades were divided into 0–4 grades, depending on the severity of the symptoms according to the method part of Dong [ 49 ]. The disease index was calculated using the following formula: Disease index (%) = × 100.…”
Section: Methodsmentioning
confidence: 99%
“…After three weeks, disease grades were recorded. The disease grades were divided into 0-4 grades, depending on the severity of the symptoms according to the method part of Dong [52]. The disease index was calculated using the following formula: Disease index (%) = ×100.…”
Section: Evaluation Of Exogenous Ethephon On Foc and Cucumber Seedlingsmentioning
confidence: 99%